AOA-2 Derivatives as Outer Membrane Protein A Inhibitors for Treatment of Gram-Negative Bacilli Infections - Ayerbe-Algaba, Rafael; Bayó, Nuria; Verdú, Ester; Parra-Millán, Raquel; Seco, Jesús; Teixidó, Meritxell; Pachón, Jerónimo; Giralt, Ernest; Smani, Younes (Frontiers in Microbiology, 2021)
Previously, we identified that a cyclic hexapeptide AOA-2 inhibited the interaction of Gram-negative bacilli (GNB) like Acinetobacter baumannii, Pseudomonas aeruginosa and Escherichia coli to host cells thereby preventing the development of infection in vitro and in a murine sepsis peritoneal model. In this work, we aimed to evaluate in vitro a library of AOA-2 derivatives in order to improve the effect of AOA-2 against GNB infections. Ten AOA-2 derivatives were synthetized for the in vitro assays. Their toxicities to human lung epithelial cells (A549 cells) for 24 h were evaluated by determining the A549 cells viability using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. The effect of these peptide derivatives and AOA-2 at 250, 125, 62.5 and 31.25 µg/mL on the attachment of A. baumannii ATCC 17978, P. aeruginosa PAO1 and E. coli ATCC 25922 strains to A549 cells was characterized by adherence and viability assays. None of the ten derivatives showed toxicity to A549 cells. RW01 and RW06 have reduced more the adherence of ATCC 17978, PAO1 and ATCC 2599 strains to A549 cells when compared with the original compound AOA-2. Moreover, both peptides have increased slightly the viability of infected A549 cells by PAO1 and ATCC 25922 than those observed with AOA-2. Finally, RW01 and RW06 have potentiated the activity of colistin against ATCC 17978 strain in the same level with AOA-2. The optimization program of AOA-2 has generated two derivatives (RW01 and RW06) with best effect against interaction of GNB with host cells, specifically against P. aeruginosa and E. coli.